Pengembangan Media Belajar Literasi Digital Berbasis Game Edukasi untuk Siswa Kelas 2 SD - Dina Salsabella Utami; Agustina Tyas Asri Hardini (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The purpose of this study is to increase the interest in reading from the problem of low interest in reading in grade 2 elementary students, with several factors of problems from low interest in reading and low reading skills of students are still lacking, the rise of types of entertainment such as playing games and watching TV so as to influence the attention of students choosing not to read. Researcher develop digital literacy learning media based on educational games by developing students to be able to play puzzles and read. With the media design created by Researcher, namely the collaboration between writing, images, and sounds, it is very important in communication and conveying messages to students, if students still do not know the word, they can see pictures and sounds that can help children in visualizing stories in reading. Researcher designed this media so that students can be interested and motivated and more enjoyable in digital literacy. Researcher used a type of development research (R&D) and a qualitative descriptive approach to percentage. For data analysis techniques that have been conducted consists of preliminary studies, product development, validity tests and conclusion drawing. The results of this study after analysis of the data of the assessment of material expert validation test by 100% and media experts by 84.2%, with the results have been qualified and eligible to be tested after improvement according to the advice of experts.